Does tooth loss in the mandibular posterior region have an effect on the mental index and panoramic mandibular index? - Kahraman Güngör; Özge Karadağ; Zühre Akarslan; Gülsün Akay (Istanbul University, 2019)
Purpose Mental index (MI) and panoramic mandibular index (PMI) are important radiomorphometric indices used for assessing the quality of the mandibular bone. The aim of this study was to investigate the possible effect of mandibular posterior tooth/teeth loss in young adults on the MI and PMI (superior panoramic mandibular index: PMI-s, and inferior panoramic mandibular index: PMI-i). Materials and Methods Digital panoramic radiographs belonging to 253 patients aged between 18-35 years old were examined. According to the inclusion criteria of the study, a patient and control group was formed. The patient group (n=46) included individuals having at least one extracted tooth in the posterior region of the mandible, and the control group (n=45) included full dentate patients. The MI and PMI (PMI-i and PMI-s) were calculated bilaterally for all of the individuals. Results No significant difference was found between the MI, PMI-i and PMI-s indices of the patient group and the control group among both genders (p>0.05). Conclusion The mandibular premolar and/or molar teeth loss in young adults did not lead to any change in the MI, PMI-i and PMI-s indices among both genders.